Aripiprazole treatment for patients with schizophrenia: from acute treatment to maintenance treatment. (November 2011) - Park, Min-Hyeon; Han, Changsu; Pae, Chi-Un; Lee, Soo-Jung; Patkar, Ashwin A; Masand, Praksh S; Fleischhacker, Wolfgang W
The most current treatment guidelines for schizophrenia recommend more than 1 year of maintenance therapy after the first psychotic episode, and more than 5 years of maintenance therapy after multiple psychotic episodes. Approximately two-thirds of such patients are known to relapse within 1 year and almost 90% of such patients may recur within 2 years. To maintain adequate consistent treatment, balancing the efficacy and safety/tolerability should be one of the most important clinical issues. In this respect, aripiprazole appears to be a good treatment option owing to its comparable efficacy, favorable safety and tolerability profile, including low incidence of parkinsonian symptoms, lack of prolactin elevation, decreased adrenergic and anticholinergic side effects, less weight gain and low incidence of metabolic syndrome. Hence this article aims to summarize the currently available clinical trial data of aripiprazole published from a number of large-scale randomized controlled studies, including a newer formulation of intramuscular injection as well as a once-monthly intramuscular depot formulation, to update knowledge of treatment options in patients with schizophrenia.